Representative versus Direct Democracy: The Role of Informational Asymmetries - Anke Kessler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
The paper studies the relative merits of direct and representative legislation in a setting where voters are uncertain both with respect to the likely consequences of different policies and with respect to the political preferences of their fellow citizens. Under representative legislation, the latter translates into uncertainty on the elected official's future policy intentions which involves a loss of control. The resulting discretionary power, however, also leads officials to endogenously acquire competence on the issues they oversee and specialize in policy formation. Policies determined in representative democracies are therefore better tailored to relevant contingencies but less close to the preferences of a majority than those determined in popular ballots. It is shown that the extent of the resulting trade-off depends on the set of alternatives among which the policy is to be chosen. Two extensions, referenda and the possibility of re-election, are briefly considered.
Keywords: D61; D78; 330; Direct Democracy; Representative Democracy; Constitutional Choice; Delegation; Asymmetric Information